Using Breeding Populations With a Dual Purpose: Cultivar Development and Gene Mapping—A Case Study Using Resistance to Common Bacterial Blight in Dry Bean (Phaseolus vulgaris L.) - Simons, Kristin J.; Oladzad, Atena; Lamppa, Robin; Maniruzzaman,; McClean, Phillip E.; Osorno, Juan M.; Pasche, Julie S. (Frontiers in Plant Science, 2021)
Dry bean (Phaseolus vulgaris L.) is an important worldwide legume crop with low to moderate levels of resistance to common bacterial blight (CBB), caused by Xanthomonas axonopodis pv. phaseoli. A total of 852 genotypes (cultivars, preliminary and advanced breeding lines) from the North Dakota State University dry bean breeding program were tested for their effectiveness as populations for genome-wide association studies (GWAS) to identify genomic regions associated with resistance to CBB. The genotypes were evaluated in the greenhouse for disease resistance at both the unifoliate and trifoliate stages. At the unifoliate stage, 35% of genotypes were resistant while 25% of genotypes were resistant at the trifoliate stage. Libraries generated from each genotype were sequenced using the Illumina platform. After filtering for sequence quality, read depth, and minor allele frequency (MAF), 41,998 SNPs and 30,285 SNPs were used in GWAS for the Middle American and Andean gene pools, respectively. One region near the distal end of Pv10 near the SAP6 molecular marker, from the Andean gene pool explained 26.7-36.4% of the resistance variation. Three to seven regions from the Middle American gene pool contributed to the 25.8-27.7% of the resistance, with the most significant peak also near the SAP6 marker. Six of the eight total regions associated with CBB resistance are likely the physical locations of QTLs identified from previous genetic studies. The two new locations associated with CBB resistance are located at Pv10:22.91-23.36 and Pv11:52.4. A lipoxgenase-1 ortholog on Pv10 emerged as a candidate gene for CBB resistance. These results provide a foundational SNP data set, improve our understanding of CBB resistance in dry bean, and impact resource allocation within breeding programs as breeding populations may be used for dual purposes: cultivar development as well as genetic studies.